Pengobatan Sendiri Sakit Kepala, Demam, Batuk Dan Pilek Pada Masyarakat Di Desa Ciwalen, Kecamatan Warungkondang, Kabupaten Cianjur, Jawa Barat - Supardi, Sudibyo; Notosiswoyo, Mulyono (Majalah Ilmu Kefarmasian, 2005)
The self-medication is an effort conducted by the community to cure theirselves using medicine, traditional medicine or others without health proffesional advice. The aims of this study are to know healthy Â– illness concept, to know local language, symptoms, cause, prevention and curation of headache, fever, cough and common cold, and the self- medication practice on the village community. This study using qualitative design and data was collected by depth interviewing from 12 key informans at Ciwalen village, Warungkondang sub-district, Cianjur district, West Java, in 1998. Key informans are the chief of RT, the chief of RW, the teachers of elementary school, the health cadres, and the housewives. Data were analyzed using triangulation methode and confirmating the interview result to the key informans. The conclussion of this study are The healthy-illness concept does not only physical aspect, but also social culture aspect. The light illness - heavy illness concept depends on the physical condition of patient, the daily activity and the medication. The community use generally local language nyeri sirah for the headache, muriang for the fever, gohgoy for the cought and salesma for the common cold. The cause of illness is commonly their physical environment, include bacteria for the cought. The prevention of illness is generally conducted by avoiding its cause. The self-medication practice generally use the medicine that were bought from the retail at their village, some of them use the traditional medicine. Reason of self-medication practice are light illness, inexpensive, time eficiency, and as a first aid before going to the health proffesional or health center. The self-medication practice is improperly done, because the community mostly bought a small amount of medicine, so that the brochure of the medicine can not be read.